Catalytic Transesterification Of Coconut Oil In Biodiesel Production: A Review - Aisyah Fathiah Ahmad; Nursyamimi Zulkurnain; Salmiah Jamal Mat Rosid; Azman Azid; Azizah Endut; Susilawati Toemen; Salwani Ismail; Wan Nazwanie Wan Abdullah; Siti Maisarah Aziz; Nurulhuda Mohammed Yusof; Sarina Mat Rosid; Nur Atiqah Nasir (Springer, 2024)
Indexed by WOS/SCOPUS/ERA